Chromosomal Aberrations in Peripheral Blood Lymphocytes in Brick Kilns Workers - A. Auda , Nazar; M. T. Jaafar, Zainab; O. Mohmmed, Sa’adyia (Iraqi Journal of Science, 2023)
This study was conducted on the workers of the brick kilns at Al- Nahrawan area south-east of Baghdad city to investigate the effect of the pollutant emissions (fumes and gases) released from the burned fuel in this kiln. Blood samples were taken from group individuals of workers at this brick kilns and non-working individuals as a control. The influence of these emissions on the workers’ health was measured by examining certain chromosomal aberrations among the workers. These aberrations were a formation of: chromosomal rings, dicentric chromosomes, breaks arm and acentric fragments. It has been observed that most of these aberrations were found within workers of age 40 years and above, represented by formations of averages 1.50 and 1.02 for chromosomal rings and fragments respectively, whereas the results of the group of age range 10-19 years old showed chromosomal aberration types (ring 0.05, dicentric 0.2, chromosomal break 0.15 and acentric fragment 0.05) while the control results for all chromosomal aberrations (ring 0.09 dicentric 0.07, chromosome break 0.12 and acentric fragment 0.10). An increase in levels of dicentric chromosomes, chromosome breaks and acentric fragments were observed in the group of age 40 years and above (0.25, 1.50 and 1.25) respectively. All these chromosomal aberrations showed significant differences when compared to the results of groups 10-19 years of age. The results also demonstrated a relation between smoking and serving years of workers, showing (0.27, 0.28 , 1.26 and 1.12) a significant increases in chromosomal aberrations (ring, dicentric, breaks and acentric fragments) at worker group of serving years 16-20 years (0.23, 0.25, 1.28 and 1.30) and group of 21-25 years (0.27, 0.28, 1.26 and 1.12) respectively comparing with healthy individuals of chromosomal aberrations types (ring 0.05, dicentric 0.20, chromosomal breaks 0.15 and acentric 0.05) Respectively. The aim of study is to investigate the effect of gases emission on chromosomes in brick kiln workers.